Spiral staircase, David Sassoon Clock Tower - Ghosh, Ayan (2023)
The clock tower and buildings in its vicinity served as an early example of controlled development, retaining a common set of building rules, raw materials, and architectural style. The ensembles of buildings are the only examples of the Neo-Palladian styles, making them visually distinct and important in the evolution of Mumbai’s architectural heritage.